2019
DOI: 10.3389/fpsyg.2019.01103
|View full text |Cite
|
Sign up to set email alerts
|

Are Working Memory Training Effects Paradigm-Specific?

Abstract: A randomized controlled trial compared complex span and n-back training regimes to investigate the generality of training benefits across materials and paradigms. The memory items and training intensities were equated across programs, providing the first like-with-like comparison of transfer in these two widely used training paradigms. The stimuli in transfer tests of verbal and visuo-spatial n-back and complex span differed from the trained tasks, but were matched across the untrained paradigms. Participants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 33 publications
7
37
0
Order By: Relevance
“…Paradigm appears to represent a boundary condition transfer, consistent with many previous studies investigating transfer across different categories of WM task (e.g. Dunning & Holmes, 2014;Gathercole et al, 2019;Holmes et al, 2019;Li et al, 2008;Minear et al, 2016;Sprenger et al, 2013;. While there was evidence favouring transfer to untrained backward recall tasks, there was no evidence for transfer to n-back following BDR training, even when it contained the same materials as the training activity (digits).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Paradigm appears to represent a boundary condition transfer, consistent with many previous studies investigating transfer across different categories of WM task (e.g. Dunning & Holmes, 2014;Gathercole et al, 2019;Holmes et al, 2019;Li et al, 2008;Minear et al, 2016;Sprenger et al, 2013;. While there was evidence favouring transfer to untrained backward recall tasks, there was no evidence for transfer to n-back following BDR training, even when it contained the same materials as the training activity (digits).…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies investigating within-paradigm transfer to untrained tasks containing memory items from a different domain (e.g. verbal digits to spatial locations) have produced mixed results (Anguera et al, 2012;Blacker, Negoita, Ewen, & Courtney, 2017;Bürki, Ludwig, Chicherio, & de Ribaupierre, 2014;Buschkuehl, Hernandez-Garcia, Jaeggi, Bernard, & Jonides, 2014;Holmes et al, 2019;Jaeggi, Buschkuehl, Perrig, & Meier, 2010;Küper & Karbach, 2016;Li et al, 2008;Minear et al, 2016;Soveri, Karlsson, Waris, Grönholm-Nyman, & Laine, 2017). Evidence points to a high degree of domain specificity in the mechanisms involved in encoding and maintaining verbal and visuo-spatial short-term memory (Alloway, Gathercole, & Pickering, 2006;Baddeley, Papagno, & Vallar, 1988;Della Sala, Gray, Baddeley, Allamano, & Wilson, 1999;Pearson, Ball, & Smith, 2014), but whether stimulus domain is a barrier to transfer was an open question.…”
Section: Introductionmentioning
confidence: 99%
“…This has sparked interest in understanding the task features that must overlap for transfer to occur (e.g. Byrne, Ewbank, Gathercole, & Holmes, 2019;Gathercole, Dunning, Holmes, & Norris, 2019;Holmes, Woolgar, Hampshire, & Gathercole, 2018;Minear et al, 2016;von Bastian, Langer, Jäncke, & Oberauer, 2013). The aim of this study is to conduct a large-scale latent variable analysis using variant forms of WM tasks to investigate their underlying factor structure.…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of transfer following WM training indicate that WM tasks might group based on paradigm-specific processes. WM paradigm is a boundary condition to transfer following trainingtransfer is rarely observed across paradigms (Byrne et al, 2019;Dunning & Holmes, 2014;Gathercole et al, 2019;Holmes et al, 2018;Li et al, 2008;Minear et al, 2016;Sprenger et al, 2013;Thompson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the evidence indicates that existing computer-based training programmes consistently produce gains on the trained tasks and closely related memory tasks [17][18]. It has been suggested that to improve the therapeutic value of WM training, it may be necessary to embed it within typical classroom activities that are ecologically valid [19].…”
Section: Rationale For Developing An Intervention That Targets Wmmentioning
confidence: 99%